(untitled) (Journal of Multidisciplinary Sciences and Innovations, 2025)
This article delves into the multifaceted concept of poverty, examining its economic significance and the theoretical frameworks that underpin its understanding. By exploring various definitions and measurements of poverty, we highlight how economic theories, including classical, neoclassical, and Marxian perspectives, inform policy approaches and interventions. The analysis also addresses the limitations of purely monetary measures, advocating for a broader view that encompasses multidimensional poverty indicators such as health, education, and living standards. Furthermore, we discuss the implications of poverty on economic growth and social stability, suggesting that a comprehensive understanding of its economic meaning is crucial for developing effective poverty alleviation strategies.